Role of Orexin-B/Orexin 2 receptor in myocardial protection. (4th April 2019) - Imperatore, Roberta; Cristino, Luigia
Abstract : Emerging evidence attributes to orexins/hypocretins (ORs) a protective function in the regulation of cardiovascular responses, heart rate, and hypertension. However, little is known about any direct effect of orexins in the heart function. This is of special relevance considering that cardiovascular diseases, including myocardial infarction and heart failure, are one of the major causes of mortality in the world. In the article published in Clinical Science (2018) (vol. 132, 2547–2564), Patel and colleagues investigated the role of orexins in myocardial protection. Intriguingly, they revealed a source of orexin-A (OR-A) and orexin-B (OR-B) in the heart and cardiomyocytes of the rat. More interestingly, these peptides exert a direct effect on the heart rate by acting in an autocrine/paracrine manner on their respective receptors (OXRs). Indeed, OR-B, but not OR-A, by acting through orexin receptor-2 (OX2R), exerts direct cardioprotective effects in heart failure models. OR-B/OX2R signalling enhances myosin light chain (MLC) and troponin-I (TnI) phosphorylation in a dose-dependent manner, leading to an increase in the strength of their twitch contraction. This effect is mediated by extracellular signal-regulated kinase 1/2 (ERK1/2) and Akt phosphorylation, both in the rat myocardial tissue and human heart samples. A negative correlation between OX2R expression and clinical severity of symptoms has been found in patients with heart failure. Thus, in addition to the known central effects of orexins/OX2R, the work of Patel and colleagues ( Clinical Science (2018)132, 2547–2564) reports a direct action of OR-B on the heart rate pinpointing to OX2R as a potential therapeutic target for prevention and treatment of cardiovascular disease.